Human papillomavirus type 16 and 18 L1 protein peptide binding to VERO and HeLa cells inhibits their VLPs binding (2003)
Human papillomaviruses (HPVs) are the cause of epithelial lesions, HPV type 16 and type 18 being associated with the development of anogenital cancer. The L1 Major Capsid Protein (L1) represents about 90% of total HPV protein and is involved in virus?host cell interaction, but little is known about this binding process. L1 sequences from HPV types 16 and 18 were synthesized in 56 20?mer peptides, covering the entire protein, HPLC?purified, 125I?radiolabeled and tested in VERO and HeLa cell?binding assays to identify those peptides with high specific binding activity. Peptides 18283 (residues 54–77) and 18294 (274–308) from HPV16 L1, as well as 18312 (59–78) and 18322 (259–278) from HPV18 L1, presented high specific target cell binding activity. Peptide 18283 and 18294 affinity constants were 300 and 600 nM, respectively. Enzyme cell treatment before binding assay indicated that VERO and HeLa cell peptide receptor is a surface?exposed protein. There was a 60% reduction in peptide 18283 binding to heparin lyase?treated cells. Cross?linking assays showed that these proteins molecular weights were around 69 and 54 kDa. Peptides 18283 and 18294 specifically inhibited HPV?16 VLP binding to HeLa cells. According to the L1? and VLP?reported structure, both peptides are close on the VLP?surface, belonging to the outer surface broad pockets suggested as being potential receptor sites. Furthermore, it has been reported that a conserved motif from peptide 18294 is the target for neutralizing antibodies. These results suggest that such binding sequences are used by the virus as cell?binding regions.